Dietrich Bonhoeffer and Asian Contextual Theology in relation to Minjung and Prajna of Inter-being - Chung, Paul S. (Dialog, 2006)
Dietrich Bonhoeffer remains an influential figure in inspiring Asian contextual theology of minjung (the poor). In addition to political reading of minjung, a Buddhist wisdom (prajna) offers a basis for understanding of religious dimension of minjung. However, there has been no discussion about Bonhoeffer's legacy of theology after Auschwitz in critical dialogue with Asian contextual theology.